Expression and Transcriptional Regulation of Individual Pregnancy-specific Glycoprotein Genes in Differentiating Trophoblast Cells - Camolotto, Soledad Andrea (2010)
Human pregnancy-specific glycoproteins (PSGs), encoded by eleven highly conserved genes, are the major placental polypeptides. Low PSG levels in maternal circulation have been associated with complicated pregnancies. However, expression of each PSG gene and their regulation during cytotrophoblast cell differentiation remain poorly explored. Herein, we analyze the expression of five PSG genes and demonstrate that they are almost undetectable in undifferentiated trophoblast, but are all transcribed in differentiated cells. Among them, PSG1, PSG3 and PSG5 genes achieve high mRNA levels while PSG7 and PSG9 are poorly expressed. In addition, total PSG proteins and transcripts markedly increase during trophoblast differentiation, preceding morphological syncytialization and βhCG expression. The 5′ regulatory region contributes to the transcriptional control of PSG gene induction in trophoblast cells undergoing differentiation. This responsive region in PSG3 maps within a 130 bp promoter sequence, which overlaps the transcription start site and requires a functional Retinoic Acid Responsive Element (RARE) and a GA-binding protein (GABP) consensus site for basal and differentiation-dependent promoter activity, respectively. Present findings provide novel data for understanding the control of PSG gene expression and demonstrate that their proteins and transcripts represent early markers of trophoblast differentiation.